SOSIALISASI PROSEDUR KESELAMATAN DAN KESEHATAN KERJA DALAM PENGOPERASIAN PESAWAT ANGKAT DI SMK KAL 2 SURABAYA : SOCIALIZATION OF SAFETY AND HEALTH PROCEDURES IN THE OPERATION OF LIFTING EQUIPMENT AT SMK KAL 2 SURABAYA - Prawirosastro, Kuncowati; Malik, Djamaludin; Sugiarti, Dwi Lucky; Saiang, Heni Yolanda; Dwireswati, Eka Rahayu; Pramawati, Dyah Ayu; Pradana, Yongki Setya; Adi Setya, Rangga Surya; Yasmine, Olivia melanie (Jurnal Pengabdian Masyarakat Pesisir, 2025)
SMK KAL 2 Surabaya is a maritime-based vocational high school that prepares skilled human resources in the shipping sector. Graduates of SMK KAL 2 are directed to work on commercial ships, especially those that operate lift aircraft as part of loading and unloading activities, but the level of students' understanding of K3 procedures, especially in the context of shipping and the operation of lift aircraft, is still low. The purpose of this community service is to hold socialization of K3 procedures for the operation of lift aircraft on ships that are expected by graduates of SMK KAL 2 so that students understand and have awareness of the importance of K3 procedures in the operation of lift aircraft on ships, can identify work risks independently, and comply with safety procedures when working on ships, Community service activities in the form of socialization of Occupational Safety and Health (K3) procedures in the operation of lift aircraft at SMK KAL 2 Surabaya have been successfully carried out with a very good level of achievement. The main target of the activity, which is to increase the understanding and awareness of students and shipping teachers on the importance of implementing K3 procedures, was achieved significantly, as evidenced by the results of the pre-test and post-test, which showed an increase in the average score of the participants.